Trophic Plasticity of the Highly Invasive Topmouth Gudgeon (Pseudorasbora parva) Inferred From Stable Isotope Analysis - Rolla, Matteo; Consuegra, Sofia; Garcia de Leaniz, Carlos (Frontiers in Ecology and Evolution, 2020)
A wide trophic niche and high trophic plasticity are often invoked to explain the successful establishment of many aquatic invaders, but there is little information regarding the diet of most invasive fish in European waters. We combined stomach content and stable isotope analysis (SIA) of 13C and 15N to examine the trophic niche of the highly invasive topmouth gudgeon (Pseudorasbora parva) in four contrasting ponds and reservoirs in South Wales. Marked differences in diet and trophic position were found among neighbouring systems only a few kilometres apart. The most diverse diet was found in ponds with the fewest number of inter-specific competitors, and resulted in topmouth gudgeon having the highest condition factor, the widest variation in δ13C and δ15N values, and the highest carbon content, typical of generalist feeders. In contrast, topmouth gudgeon that coexisted with other cyprinids, were much more likely to have empty stomachs and relied almost exclusively on plant seeds, resulting in fish having a poor condition factor and low trophic position. Comparisons with other trophic studies indicate that variation in isotope values among neighbouring sites can exceed variation across continents, making it difficult to predict the diet or trophic impacts of the invasive topmouth gudgeon. Given the importance of obtaining reliable data on trophic position for risk assessment, our study shows that the use of SIA could be used to prioritize control and eradication measures that take into account trophic plasticity.